2014
DOI: 10.7880/abas.13.315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Job Type on Perspective Index

Abstract: In this study, all employees (including part-time employees) of a shinkin bank were surveyed using the organizational activation diagnostic tool "oractika," developed by Takahashi (1997). Similar to Takahashi (2014), the results of the survey confirmed a mostly linear, positive relationship between the perspective index and job satisfaction and a mostly linear, negative relationship between the perspective index and the desire to quit one's job. In other words, as the perspective index increases, job satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…However, the subjects of this study were full-time rather than part-time employees. Okada and Inamizu (2014) also noted that part-time employees have a greater tendency to be turnover candidates than full-time employees. They also hypothesized that part-time employees dissatisfied with their jobs would leave them, while satisfied part-time employees would remain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the subjects of this study were full-time rather than part-time employees. Okada and Inamizu (2014) also noted that part-time employees have a greater tendency to be turnover candidates than full-time employees. They also hypothesized that part-time employees dissatisfied with their jobs would leave them, while satisfied part-time employees would remain.…”
Section: Resultsmentioning
confidence: 99%
“…Okada and Inamizu (2014) analyzed part-time employees at Shinkin Bank, and they reported that part-time employees have a high job satisfaction level compared to full-time employees. However, the subjects of this study were full-time rather than part-time employees.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there is a great deal of research on job satisfaction and related factors (e.g., Inamizu, 2015;Okada & Inamizu, 2014;Takahashi, Ohkawa, & Inamizu, 2014a;Takahashi, Ohkawa, & Inamizu, 2014b). However, according to Schaufeli and Bakker (2010), while there is much overlap with job satisfaction, WE and job satisfaction are two different concepts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Takahashi, Okawa, & Inamizu (2014a, 2014b) conducted a longitudinal study of a certain corporation's restructuring to show that a spurious correlation may exist between job satisfaction and self-determination (a construct of intrinsic motivation) and further suggested that the perspective index is a true factor in job satisfaction. In fact, many studies have shown the perspective index to be a factor in job satisfaction (Inamizu, 2015a;Okada & Inamizu, 2014;Tahakashi, 1997Tahakashi, , 2013Tahakashi, , 2014.…”
Section: Introductionmentioning
confidence: 99%